New method of defining existing deformities and new operative procedure for correcting the deformities in the congenital clubfeet (Hussain’s procedure)- early results in primary surgery. - Lakhey, RB (Journal of Institute of Medicine Nepal, 2016)
Abstract: Introduction: A new method of defining the existing/persisting deformities in congenital clubfoot and a new operative procedure for correcting the deformities has been proposed. Methods: We retrospectively evaluated 43 feet of 30 patients (12 girls, 18 boys) who underwent the new surgical procedure for congenital clubfoot. The patients were evaluated with Cummings’ modification of Laaveg and Ponseti score. The mean duration of follow-up was 10.7 months. Results: 81.3% of the cases of the idiopathic congenital clubfoot had excellent results, 16.2% had good results and 2.3% had fair results, when managed primarily with the new method of clubfoot treatment. Conclusion: While using the new method, exact existing/persisting deformities can be pointed out and adequate correction of the deformities can be done; thus there is less risk for over-and under-correction. The early results show that this method is effective. Long term results are awaited.